Identification and Molecular Docking Study of a Novel Angiotensin-I Converting Enzyme Inhibitory Peptide Derived from Enzymatic Hydrolysates of Cyclina sinensis - Fangmiao Yu; Zhuangwei Zhang; Liwang Luo; Junxiang Zhu; Fangfang Huang; Zuisu Yang; Yunping Tang; Guofang Ding (Marine Drugs, 2018)
Marine-derived angiotensin-I converting enzyme (ACE) inhibitory peptides have shown potent ACE inhibitory activity with no side effects. In this study, we reported the discovery of a novel ACE-inhibitory peptide derived from trypsin hydrolysates of Cyclina sinensis (CSH). CSH was separated into four different molecular weight (MW) fractions by ultrafiltration. Fraction CSH-I showed the strongest ACE inhibitory activity. A peptide was purified by fast protein liquid chromatography (FPLC) and reversed-phase high-performance liquid chromatography (RP-HPLC) and its sequence was determined to be Trp-Pro-Met-Gly-Phe (WPMGF, 636.75 Da). The Lineweaver-Burk plot showed that WPMGF was a competitive inhibitor of ACE. WPMGF showed a significant degree of stability at varying temperatures, pH, and simulated gastrointestinal environment conditions. We investigated the interaction between this pentapeptide and ACE by means of a flexible molecular docking tool. The results revealed that effective interaction between WPMGF and ACE occurred mainly through hydrogen bonding, hydrophobic interactions, and coordination bonds between WPMGF and Zn(II). In conclusion, our study indicates that a purified extract derived from Cyclina sinensis or the WPMGF peptide could potentially be incorporated in antihypertensive functional foods or dietary supplements.